PEMBUATAN COOKIES BEKATUL (KAJIAN PROPORSI TEPUNG BEKATUL DAN TEPUNG MOCAF) DENGAN PENAMBAHAN MARGARINE (UPN VETERAN JAWA TIMUR, 2016)
ABSTRACTCookies is a type of baked snacks. The proportion of bran flour and mocaf in bran cookies production is expected to add to the nutritional value, because the chemical constituents in the flour bran is an essential nutrient for the body such as fiber, protein, vitamin B and vitamin E. The addition of bran in products cookies cause cookies to be loud so that added margarine in bran cookies. The addition of margarine is expected to provide improved crispness, improve texture and enhance flavor. This study aims to determine the effect of the proportion of bran flour and mocaf flour with the addition of margarine on the quality of the physico chemical and organoleptic. The study of bran cookies using Complete Random Design (RAL) factorial with two factor and each treatment combination was repeated 2 times. The first factor, proportions of bran flour and flour mocaf (20:80; 40:60; 60:40). The second factor, addition margarine (75 %; 85%; 95%) The results of the study indicate the best treatment cookies bran derived from rice bran and mocaf flour combination (40%: 60%) with addition of 95% margarine. The bran cookies had the characteristic moisture content of 4.601%, protein 3.82% , fat 37.87%, and organoleptic test : sense 69, color 71, crispiness 65.Keyword: Rice Bran, Cookies, Margarine, MocafABSTRAKCookies atau kue kering merupakan jenis makanan ringan yang dipanggang. Proporsi tepung bekatul dan tepung mocaf dalam pembuatan cookies bekatul diharapkan dapat menambah nilai gizi dalam produk cookies, karena kandungan kimia yang ada di dalam tepung bekatul merupakan zat gizi penting untuk tubuh seperti serat, protein, vitamin B dan vitamin E. Penambahan bekatul dalam produk cookies menyebabkan cookies menjadi keras sehingga ditambahkan margarine dalam cookies bekatul diharapkan dapat memberikan peningkatan kerenyahan, memperbaiki tekstur dan meningkatkan cita rasa. Penelitian ini bertujuan untuk mengetahui pengaruh proporsi tepung bekatul : tepung mocaf dengan penambahan margarine terhadap kualitas fisika kimia dan organoleptik cookies bekatul yang dihasilkan.Penelitian menggunakan Rancangan Acak Lengkap (RAL) pola faktorial dengan 2 faktor dan masing-masing perlakuan kombinasi diulang sebanyak 2 kali. Faktor I proporsi tepung bekatul : tepung mocaf ( 20:80 ; 40:60 ; 60:40). Faktor II penambahan margarine (75 ; 85 ; 95).Hasil penelitian menunjukkan cookies bekatul perlakuan terbaik diperoleh dari kombinasi tepung bekatul : tepung mocaf (40% : 60%) dengan penambahan margarine 95%. Cookies bekatul tersebut mempunyai karakteristik dengan kadar air 4,601%, kadar protein 3,82%, kadar lemak 37,87%, dan hasil uji organoleptik dengan nilai rata-rata terhadap rasa 69, warna 71, kerenyahan 65.Kata Kunci: Bekatul, Cookies, Margarine, Mocaf